THE EFFECT OF DIRECT INTERACTION STRATEGY IN TEACHING READING COMPREHENSION AT EIGHT GRADE OF MTS PONPES DARUL QURAN MEDAN - Mada, Omivia (Faculty of Tarbiyah nad Teacher Training, 2021)
This research aimed to find out The Effect of Direct Interaction Strategy in Teaching Reading Comprehension in Narrative Text at the Eight Grade of MTS Ponpes Darul Quran Medan in 2020/2021 Academic Year. The population of the research was the eight grade student that amount 53 students consist of two classes. The research methodology was an experimental research, which conducted the experimental class (VII1 -1 ) and control class (VII1-2) as sample. The result of the research shown that The Effect of Direct Interaction Strategy In Teaching Reading Comprehension at Eight Grade of MTS Ponpes Darul Quran Medan in 2020/2021 Academic Year can be describe as below: the average of the score 76,55 with the highest score is 92 and the lowest score is 62 (by using Direct Interaction Strategy) and the average of the score is 59,45 with the highest score is 86 and the lowest score is 54 (by using Conventional Method)The test consist of two types, namely pre-test and post-test, the data were analized by using t-test formula. After analyzing the data, the result of the research show that the value of t-count wash higher than the value of t-table 11,277> 2,000 at the level significant of a =0.05 and at the degree of freedom (df)= 51. It was indicated there is the significant effect of direct interaction strategy in teaching reading comprehension, and the alternative hypothesis (Ha) was accepted and hypothesis (Ho) was rejected.